MODERN TECHNOLOGIES IN THE DIAGNOSIS OF THE VISION ORGAN PATHOLOGY IN PATIENTS WITH NEUROFIBROMATOSIS TYPE I (REVIEW OF LITERATURE) - A. S. Ol’shanskaya; N. A. Shnayder; D. V. Dmitrenko; E. V. Kozina; E. Yu. Chesheyko; A. V. Dyuzhakova (Русский журнал детской неврологии)
The review provides information on the nature and the modern methods of diagnosis of vision organ disorders in patients with neurofibromatosis type I (NF-I). The review of available full text publications in foreign and Russian databases is carried out. Presented literature review indicates a high variability of vision organ disorders in NF-I in the clinical course (slowly progressive, stationary, and rapidly progressive), severity (from asymptomatic to severe disabling), and clinical forms. During the observation of patients (probands) with NF-I and their family members, a comprehensive examination, accompanied by widespread introduction into clinical practice of modern diagnostic methods, including dynamic control of asymptomatic members of family genealogy, is important. The multidisciplinary approach has great significance for diagnostics, treatment and dispensary observation of NF-I.